2011
DOI: 10.3109/14767058.2010.545907
|View full text |Cite
|
Sign up to set email alerts
|

Antepartum and postpartum maternal plasma levels of E-selectin and VE-cadherin in preeclampsia, gestational proteinuria and gestational hypertension

Abstract: We found no changes in VE-cadherin levels in preeclamptic groups. Increased antepartum and postpartum levels of sE-selectin in women with SPE and GP suggest that endothelial dysfunction may be one of the key processes in the pathogenesis of PE and the underlying mechanism, as well, that links PE with cardiovascular disease in later life. GP, also, appears to be a mild variant of PE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Cellular forms of these molecules can be detected in the blood, and their levels are altered dramatically in conditions such as sepsis, acute coronary syndromes and rheumatoid arthritis [9]. Circulating concentrations of the adhesion molecules P-selectin [9,10], vascular cellular adhesion molecule-1 (VCAM-1 [11,12]), E-selectin [9,10,13] and intercellular adhesion molecule-1 (ICAM-1 [9]) are reported to be elevated in women with established preeclampsia, indicating endothelial dysfunction. Few studies have examined these molecules in longitudinal studies throughout pregnancy.…”
mentioning
confidence: 98%
“…Cellular forms of these molecules can be detected in the blood, and their levels are altered dramatically in conditions such as sepsis, acute coronary syndromes and rheumatoid arthritis [9]. Circulating concentrations of the adhesion molecules P-selectin [9,10], vascular cellular adhesion molecule-1 (VCAM-1 [11,12]), E-selectin [9,10,13] and intercellular adhesion molecule-1 (ICAM-1 [9]) are reported to be elevated in women with established preeclampsia, indicating endothelial dysfunction. Few studies have examined these molecules in longitudinal studies throughout pregnancy.…”
mentioning
confidence: 98%
“…In a small study of 12 women with severe PE, there was a significant increase in soluble E-selectin (sE-selectin) in cases compared to controls at 3-6 days and then 12-15 weeks postpartum. 51 Similarly, Chambers et al reported higher levels in cases 3 years postpartum. 42 Nonetheless, other studies have demonstrated no difference in sE-selectin at 1 and 2.5 years postpartum when comparing cases and controls.…”
Section: Biomarkers Of Endothelial Function Soluble Intercellular Adh...mentioning
confidence: 90%
“…The most indicative marker of endothelium damage and dysfunction seems to be the soluble E-selectin (sE-selectin) ( Figure 3 ) [ 43 ]. Increased serum concentration of sE-selectin in patients with PE in comparison to normotensive pregnant women was identified in multiple studies [ 37 , 43 , 46 , 47 , 48 ]. Interestingly, in the study by Papakonstantinou et al [ 46 ] these differences were observed only in patients with PE, and not in patients with gestational hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Increased serum concentration of sE-selectin in patients with PE in comparison to normotensive pregnant women was identified in multiple studies [ 37 , 43 , 46 , 47 , 48 ]. Interestingly, in the study by Papakonstantinou et al [ 46 ] these differences were observed only in patients with PE, and not in patients with gestational hypertension. On the other hand, Mistry et al [ 43 ] observed a significantly higher level of sE-selectin in patients with EOP compared to patients with LOP, which indicates a correlation between levels of this marker and severity of the disease.…”
Section: Discussionmentioning
confidence: 99%